Opera omnia Desiderii Erasmi Roterodami: recognita et adnotatione critica instructa notisque illustrata / Ordo 9, Tomus 1 - Erasmus, Desiderius (Opera omnia Desiderii Erasmi Roterodami recognita et adnotatione critica instructa notisque illustrata, 1982)
Inhalt: Apologia respondens ad ea quae Iacobus Lopis Stunica taxauerat in prima duntaxat Novi Testamenti aeditione - Introduction, I. Historical background of the controversy with Stunica: the appearance of the Nouum Instrumentum (1516) and its reception, II. Jacobus Lopis Stunica and his polemics with Erasmus. His writings, III. A chronological synopsis of the thirteen polemical writings exchanged by Stunica and Carranza on the one side and Erasmus on the other, IV. Circumstances of composition of Erasmus' Apologia respondens ad ea quae Iacobus Lopis Stunica taxauerat in prima duntaxat Noui Testamenti aeditione, V. Structure and literary genre of the Apologia respondens ad ea quae Iacobus Lopis Stunica in prima taxauerat duntaxat Noui Testamenti aeditione, VI. The textual history of the Apologia respondens ad ea quae Iacobus Lopis Stunica in prima taxauerat duntaxat Noui Testamenti aeditione. The present edition - List of the editions of the Apologia respondens ad ea quae Iacobus Lopis Stunica in prima taxauerat duntaxat Noui Testamenti aeditione, Conspectus siglorum - Critical edition, List of abbreviations, Index nominum. - One of the fiercest enemies of Erasmus was the Spanish theologian Jacobus Lopis Stunica who contributed to the Computensian Polyglot that rivalled Erasmus’ New Testament edition. This second volume of the Amsterdam edition of the apologias contains the critical edition of the Latin text of one of the apologias against Stunica. The volume contains an introduction in English and a commentary which includes an identification of sources quoted, and background information elucidating the Latin text. (Verlagsinformation)